Audit report lag and the cost~of~equity capital - Md. Borhan Uddin Bhuiyan; Yimei Man; David Lont (Journal of Capital Markets Studies (JCMS), 2024)
Purpose - This research investigates the effect of audit report lag on the cost of equity capital. We argue that an extended audit report lag reduces the value of information and raises concerns for investors, resulting in an increased cost of equity capital. Design/methodology/approach - We hypothesize that audit report lag increases the firm cost of equity capital. We conduct ordinary least squares (OLS) regression analyses to examine our hypothesis. Finally, we also perform a range of sensitivity tests to examine the hypothesis and robustness of findings. Findings - Using a sample of the listed US firms from 2003 to 2018, we find that firms with higher audit report lag have a higher cost of equity capital. Our findings are economically significant as one standard deviation increase in audit report lag raises 3.82 basis points of cost of equity capital. Furthermore, our results remain robust to endogeneity concerns and alternative proxies for the cost of equity capital measures. Finally, we confirm that audit report lag increases the firm cost of equity capital through increasing information asymmetry and future financial restatement as a mediating channel. Originality/value - We contribute to the theoretical discussion about the role of audit report lag and investors' perceptions. Overall, our results suggest that audit report lag affects a firm cost of equity capital.
Keywords: 330; Audit report lag; Cost of equity capital; Information asymmetry